Electromagnetic and Thermal Analysis of Interior Permanent Magnet Motors Using Filled Slots and Hairpin Windings - Minh, D. B.; Phuong, N. H.; Quoc, V. D.; Duc, H. B. (Engineering, Technology & Applied Science Research, 2022)
This paper analyzes the electromagnetic and thermal design of interior permanent magnet motors using filled slots and hairpin windings for electric vehicle applications. Two models of ∇ shape of the interior permanent magnet motors have been proposed to evaluate the temperature distribution and cogging torque performance. A narrow opening slot of the interior permanent magnet of 48 slots/8 poles with the filled winding has been designed to investigate the electromagnetic torque because the cogging torque depends on opening stator slots. A parallel–rectangle slot of the interior permanent magnet with the hairpin winding has been also implemented with finite element analysis to evaluate their performances. Normally, the slot opening of the interior permanent magnet stator equals the slot width, it is greater than the size of hairpin windings, and the cogging torque is increased significantly with a bigger slot opening. The main advantage of the hairpin winding design is the high slot fill factors. Hence, the lower the current density, the higher torque, and efficiency are, than the normal design with the same geometry parameters. To improve the cogging torque due to the wide slot opening, the step–skew rotor slices have been arranged to minimize the torque ripple with different skewing angles.